Evaluation of morphological and physical characteristics of hazelnut varieties - Lopes, Arminda (2016)
In this study 15 hazelnut varieties existing in a collection of Viseu Agricultural Station were evaluated. The nuts were studied in respect of their morphological characteristics, such as fruit and kernel weight, index of compression and of shape and shell thickness. The study was complemented with analysis of physical properties such as colour and texture, and the determination of moisture content and water activity, given the importance that these parameters take in the conservation capacity of the fruits. All experiments followed standard methods, being also used the following equipment: texturometer, colorimeter and hygrometer. The results obtained allowed to know the expectable ranges for each color parameters in the shell, film and kernels: L*, a*, b* chroma and hue, having been found statistically significant differences among the cultivars studied. As regards the textural parameters evaluated by crust crushing and crumb cutting tests (hardness, friability and resilience) there were also significant differences. Evaluation of moisture was of great importance because confirmed that the solar drying, used to extract the excess of moisture from the fruits, was sufficient to reach low values, between 1.66% and 4.52%, being so a guarantee of preservation.